Assessing and mitigating transfer gaps through ecosystem interactions - Gileva, Tatiana; Galimova, Margarita; Khussamov, Rail; Galimov, Timur (Edelweiss Applied Science and Technology, 2024)
The purpose of this paper is to determine the most appropriate model of cooperation between an enterprise and the innovation ecosystem of the territory based on the assessment of its readiness to implement joint innovation activities. One of the requirements necessary for the effectiveness of innovation activity is to ensure the continuity of innovation processes along the entire value chain. The peculiarities of different organizations and different levels of readiness of ecosystem participants for innovation activities lead to ambiguity in the choice of possible options for partnership interactions. The paper presents a scheme of development for the territory's innovation ecosystem based on the concept of a minimum viable ecosystem. The concept of transfer gap is introduced as a violation of the continuity of the process of transfer (transfer) of the results of innovation activity along the entire value chain, which does not allow to obtain a competitive result (an innovative product) and/or bring it to the consumer within a competitive timeframe. Researchers identify two components of the transfer gap: technological and managerial. We developed indicators and scales for their assessment. On the basis of analyzing the interests and risks of participants in innovation processes in all links of the innovation chain, the possibilities of the innovation ecosystem to dampen transfer gaps are identified. We form the model of overcoming transfer gaps on the basis of partnership interactions.